Analyzing The Link Between Symptoms and Tumor Site In Colorectal Cancer Patients At Al Sheikh Zayed General Hospital, 2010-2018 - Zaid Maad Ahmed Samem; Abd Al-Salam Aziz M. Al-Khatib; Saad Fakhri Abdulrahman (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The purpose of this study is to better understand potential variables causing delays in diagnosis by examining the link between early symptoms and tumor location in colorectal cancer. Retrospective data from Hospital University Baghdad Iraq (Al sheikh zayed general hospital) patients diagnosed with colorectal cancer between 2010 and 2018 was gathered. The majority of the 212 patients in the research (43.4%) had rectal tumors, which were followed by left-sided tumors (37%) and right-sided tumors (18.9%). Upon analyzing the symptoms, it was found that rectal bleeding had a strong correlation (34%), but changes in bowel habits were more common in rectal tumors (32%) and left-sided tumors (22.6%). There was a strong correlation found between abdominal mass and right-sided tumors (7.5%) and left-sided tumors (11.3%) and intestinal obstruction. The most common sign of straining, called tendesmus, was observed in rectal tumors (8%). There was no discernible relationship between the location of the tumor and stomach discomfort. These results emphasize the need of taking early symptoms into account when identifying colorectal cancer and the necessity of customized screening and diagnostic strategies depending on the location of the tumor.